PEMBATALAN PADA PERJANJIAN YANG TIDAK MENGGUNAKAN BAHASA INDONESIA (STUDI KASUS PUTUSAN NOMOR 450/PDT.G/2012 / PN.JKT.BAR) - Thomas Aryanto G; Stanislaus Atalim (Fakultas Hukum Universitas Tarumanagara, 2018)
Starting from the treaty agreement from national agreement to international agreement, with the existence of the development of the time of course there are many developments including in the development in the field of agreement. in this journal the author explains about how should the implementation of Article 31 of Law Number 24 Year 2009 concerning about Flags, Languages, and Symbol of Country and National Anthem should be applied in Indonesia. the authors raise this issue using case studies on decision number 450 / Pdt.G / 2012 / PN Jkt.Bar where PT Bangun Karya Pratama Lestari sued Nine AM Ltd. to cancellation agreements that only use the English language without using the Indonesian language. in this case the panel of judges decides that the agreement is null and void because it violates Article 31 of Law Number 24 Year 2009 because the judges consider the agreement to violate Article 1320 Paragraph (4) of the Civil Code which reads